(untitled) (Development Service Industry Management, 2024)
The article substantiates the importance of strengthening the investment and innovation security of business entities, as a result of which their activities will provide for stable and dynamic growth. Emphasis is placed on the current difficult conditions of business activity in Ukraine, when it is constantly under the influence of hybrid and military aggression, and therefore, the processes of investment and innovative development should be considered as a priority prerequisite for strengthening national security. It is proposed to link the formation and implementation of priorities and tools for strengthening the investment and innovation security of business entities with the factors that determine the level of this type of security in relation to the country, region and industry. According to this approach, the characteristics of the toolkit of organizational, financial, economic and resource support for investment and innovation security of business entities are provided. Attention was drawn to the importance of adaptation of business entities to the influence of factors of the internal and external market environment, while avoiding or minimizing the impact of risks and threats on investment and innovation security. At the same time, the reserves of strengthening the investment and innovation security of business entities, which lie in the plane of resource provision, are such that they are easily mobilized, however, they are quickly exhausted in the process of introducing progressive technologies. It has been proven that strengthening the investment and innovation security of business entities of Ukraine under modern conditions is achieved through the involvement of progressive management tools. The importance of implementing lending tools, which allows for the formation of the necessary resource potential for the implementation of safe investment and innovation activities, is emphasized.